2020
DOI: 10.31083/j.jin.2020.03.112
|View full text |Cite
|
Sign up to set email alerts
|

Muramyl dipeptide promotes Aβ1-42 oligomer production via the nod2/p-p38 mapk/bace1 signaling pathway in the sh-sy5y cells

Abstract: The relationship between chronic bacterial colonization in the brain and Alzheimer's disease is attracting extensive attention. Recent studies indicated that the components of bacterial biofilm drive the amyloid-β production. Muramyl dipeptide, the minimal bioactive peptidoglycan motif common to all bacteria, contributes to the development of many central inflammatory and neurodegenerative disorders. However, the involvement of Muramyl dipeptide in amyloid-β production is not completely defined. In our present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…showed that MDP at 10 µg/ml induced the upregulation of phosphorylated-p38 mitogenactivated protein kinase (MAPK; Chen et al, 2020). In neurons, the MAPK signalling pathway plays an important role in the regulation of NLRP1 inflammasome expression and activation (Fann et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…showed that MDP at 10 µg/ml induced the upregulation of phosphorylated-p38 mitogenactivated protein kinase (MAPK; Chen et al, 2020). In neurons, the MAPK signalling pathway plays an important role in the regulation of NLRP1 inflammasome expression and activation (Fann et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…MDP (InvivoGen, USA) was prepared as a 10 mg/mL stock in endotoxin-free water. When used in experiments, the MDP was diluted to 100 µg/mL with serum-free media before further diluted in the samples to a final working concentration of 10 µg/mL (Chen et al, 2020).…”
Section: Aβ and Mdp Preparationmentioning
confidence: 99%
“…In turn, MDP promotes inflammatory cell infiltration in the CNS, destroys the neurovascular integrity, down-regulates cognitionrelated receptors, exacerbates the production of Aβ, and eventually contributes to neuronal damage and memory impairment. 39,40 Nod1 and Nod2 have synergistic functions in the detection of bacteria and in the inflammatory response. Early research revealed that Nod1 and Nod2 induced the activation of the NF-κB and MAPKs following recognition of bacterial components, resulting in proinflammatory cytokine and chemokine secretion.…”
Section: Recognition Receptors In Neurodegenerative Diseasesmentioning
confidence: 99%
“…The higher expression of Nod2 agitated by MDP (the muropeptide ligand of Nod2) stimulates a cascade of reactions, such as the inflammatory response and ROS. In turn, MDP promotes inflammatory cell infiltration in the CNS, destroys the neurovascular integrity, down-regulates cognition-related receptors, exacerbates the production of Aβ, and eventually contributes to neuronal damage and memory impairment. , …”
Section: Role Of the Gut Microbiota And Pattern Recognition Receptors...mentioning
confidence: 99%
“…To clarify the in ammatory priming role of IL-1β and IL-6 in BV-2 conditioned medium, IL-1β in 8 pg/mL or IL-6 in 10 µg/mL was added to ATXN3/Q 75 -GFP-expressing SH-SY5Y cells to mimic the concentration of IL-1β or IL-6 in BV-2 conditioned medium added to SH-SY5Y cells. MDP, a NLRP1 agonist upregulating Aβ-associated in ammation in the SH-SY5Y cells [29], was also included for comparison. After induction of ATXN3/Q 75 -GFP expression in SH-SY5Y cells for 6 days, the culture medium was removed and replaced with new cultural medium/conditioned medium (± LPS/IFN-γ stimulation, 2:1 ratio), MDP (0.1 µg/mL), IL-1β (8 pg/mL) or IL-6 (10 µg/mL), and further incubated for 48 h (Fig.…”
Section: Anti-in Ammatory Potentials Of Test Compounds In Lps/ifn-γ I...mentioning
confidence: 99%